2015
DOI: 10.1007/s10620-015-3711-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Fibroblast Growth Factor 21 Prevents Chemically-Induced Hepatocarcinogenesis in Mice

Abstract: Systemic administration of FGF-21 can prevent DEN-induced hepatocarcinogenesis via suppressing oxidative stress and increasing the expression of KLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
(62 reference statements)
0
12
0
1
Order By: Relevance
“…In agreement with these findings, no signs of pathological proliferation were detected in the liver of two different transgenic mouse models overexpressing FGF21 from birth (Kharitonenkov et al , ; Huang et al , ) or in mice treated with recombinant native FGF21 (Adams et al , ,b). Moreover, overexpression of FGF21 specifically in the liver in transgenic mice or treatment with native FGF21 delayed the appearance of chemically induced tumors (Huang et al , ; Xu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these findings, no signs of pathological proliferation were detected in the liver of two different transgenic mouse models overexpressing FGF21 from birth (Kharitonenkov et al , ; Huang et al , ) or in mice treated with recombinant native FGF21 (Adams et al , ,b). Moreover, overexpression of FGF21 specifically in the liver in transgenic mice or treatment with native FGF21 delayed the appearance of chemically induced tumors (Huang et al , ; Xu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of FGF-21 is reported to promote HCC in mice receiving a long-term obesogenic diet [36]. Long-term administration of FGF-21 prevents chemically induced hepatocarcinogenesis in mice [37]. However, FGF-21 is known to be expressed in several tissues, including those of the liver, fat, and pancreas [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the serum level and hepatocyte expression of FGF21 are elevated in patients with liver cancer, and the induction of FGF21 may involve P53 (14). Moreover, long‐term administration or overexpression of FGF21 was shown to prevent chemically induced hepatocarcinogenesis in mice models (39, 40). Thus, FGF21 may not be suitable for kidney protection in patients with cancer during cisplatin chemotherapy because it may suppress the chemotherapy effect.…”
Section: Discussionmentioning
confidence: 99%